Shifting scales of justice: the Supreme Court in neo-liberal India - Suresh, Mayur (ed.); Narrain, Siddharth (ed.) (Hyderabad, 2014)
This book explain, In the course of the past two decades, the Supreme Court has regulated the use of India?s forest resources; passed orders on the type of fuel to be used in urban public transport; controlled appointments to the higher judiciary
Keywords: Public Interest law